2021
DOI: 10.1149/1945-7111/ac0862
|View full text |Cite
|
Sign up to set email alerts
|

Lead-Air Electrochemical System with Acid Electrolyte

Abstract: The possibility of utilization of the lead-air electrochemical system as a power source is shown. The system consists of a standard lead electrode and H2SO4 electrolyte, used in the lead acid battery and a gas diffusion electrode developed in the Institute of Electrochemistry and Energy Systems. Three catalysts have been checked for applicability with the new system-active carbon Norit NK, cobalt tetramethoxyphenylporphyrin and cobalt phthalocyanine. Cyclic voltammetry has been applied to all three catalysts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…12 Composition modification of the electrode and the electrolyte is generally used for inhibiting metal corrosion in addition to structure optimization. 13 To inhibit hydrogen evolution reaction, Mg can be alloyed with other metals of Al, Zn, Mn, [14][15][16][17][18][19] improving the performance of Mg-air batteries. Hopkins et al 20 suppressed open-circuit corrosion by displacing electrolyte from the electrode surface with a nonconducting oil during battery standby.…”
mentioning
confidence: 99%
“…12 Composition modification of the electrode and the electrolyte is generally used for inhibiting metal corrosion in addition to structure optimization. 13 To inhibit hydrogen evolution reaction, Mg can be alloyed with other metals of Al, Zn, Mn, [14][15][16][17][18][19] improving the performance of Mg-air batteries. Hopkins et al 20 suppressed open-circuit corrosion by displacing electrolyte from the electrode surface with a nonconducting oil during battery standby.…”
mentioning
confidence: 99%
“…Another type of data, which at this stage is part of the catalogue, was derived from the Automatic recording weather station (AWG), figure 3, presented in detail in table 5. The data were generated from an in situ study (field data) done by Iliyan Popov and Boris Shirov by OXYMET 24,25,26 .…”
Section: Automatic Recording Weather Station (Awg) Datamentioning
confidence: 99%
“…Figure 3 AWG with Environmental battery 24, 25, 26 Table 5 Data and parameters that the AWG generates 24,25,26 .…”
Section: Automatic Recording Weather Station (Awg) Datamentioning
confidence: 99%
“…Recently, metal-air batteries (MABs) have emerged and been intensively studied as promising and efficient batteries for different applications [25][26][27][28][29]. They are compact and lightweight energy sources with a high energy density [28,30]. In such electrochemical systems, oxygen from the air is used as a cathode along with a liquid electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Milusheva et al [30] showed the possibility of the utilisation of the lead-air electrochemical system as a power source. This system consisted of a standard lead electrode and H 2 SO 4 electrolyte used in the lead-acid battery and a gas diffusion electrode which was sufficiently stable in the sulphuric acid electrolyte.…”
Section: Introductionmentioning
confidence: 99%